Profile of Basic Teaching Skills of Prospective Biology Teachers: A Video-Based Longitudinal Study in a Microteaching Course (2020–2023) - Maik N. R. Akobiarek; Slamet Hariyadi; Indrawati; C. Tanta (Postgraduate, University of Mataram, 2026)
This video-based longitudinal study is the first in Papua to describe the profiles of eight basic teaching skills of prospective biology teachers who took the Microteaching course from 2020 to 2023. The study was conducted at the Biology Education Program, Faculty of Teacher Training and Education, Cenderawasih University, from April to May 2024. The population in this study consisted of 180 sixth-semester students enrolled in the Microteaching course, with a random sample of 45 students (25%) selected. Data collection techniques utilized an observation sheet for basic teaching skills. The results indicated that, on average, the basic teaching skill scores of prospective biology teachers were 62.47 (± 6.61), falling into the “adequate” category. Longitudinal studies provide authentic data that can also be used to measure various classroom learning activities.